2022
DOI: 10.1002/hec.4489
|View full text |Cite
|
Sign up to set email alerts
|

Exploring physician agency under demand‐side cost sharing—An experimental approach

Abstract: Demand-side cost sharing in the health sector occurs when a patient is required to pay for a portion of medical treatment costs. Out-of-pocket payments by patients can take the form of co-payments according to a fixed fee schedule or specific co-insurance rates. Demand-side cost sharing can be the result of national policy in single-payer systems such as in the Scandinavian countries, where out-of pocket payments for various health services are set by the government. In markets where consumers may choose from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…More generally, our experimental method and findings contribute to a growing economic literature on measuring altruistic preference among medical students and physicians (e.g., Attema et al., 2023; Ge et al., 2022; Hennig‐Schmidt et al., 2011; Hennig‐Schmidt & Wiesen, 2014; Li et al., 2017; Wang et al., 2020). Using a modified dictator game, developed by Andreoni and Miller (2002) and refined by Fisman et al.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…More generally, our experimental method and findings contribute to a growing economic literature on measuring altruistic preference among medical students and physicians (e.g., Attema et al., 2023; Ge et al., 2022; Hennig‐Schmidt et al., 2011; Hennig‐Schmidt & Wiesen, 2014; Li et al., 2017; Wang et al., 2020). Using a modified dictator game, developed by Andreoni and Miller (2002) and refined by Fisman et al.…”
Section: Resultsmentioning
confidence: 77%
“…Consequently, we suggest the pandemic is the more likely explanation for reduced levels of altruism among medical students who enrolled before the pandemic. 16 More generally, our experimental method and findings contribute to a growing economic literature on measuring altruistic preference among medical students and physicians (e.g., Attema et al, 2023;Ge et al, 2022;Hennig-Schmidt et al, 2011;Hennig-Schmidt & Wiesen, 2014;Li et al, 2017;Wang et al, 2020). Using a modified dictator game, developed by Andreoni and Miller (2002) and refined by Fisman et al (2007), Li et al (2017) and Li (2018) structurally estimate the altruistic preference of medical students and found that they are less altruistic than the general US population.…”
Section: Field Experiments Among Medical School Students In Wuhanmentioning
confidence: 79%
“…The parametern denotes the relative valuation of the health benefit in n's preference function. Specifying physician preferences to comprise a combination of profit and patient benefit has been shown to fit well to experimental data (Godager & Wiesen 2013, Li et al 2017, Li 2018, Wang et al 2020, Ge & Godager 2021a, Ge et al 2022, Li et al 2022. Since our data is from a controlled experiment guaranteeing that females and males face exactly the same values of fi B , and since MRS n (B, fi) in (4) increases monotonously withn , we may conclude on the question of gender differences in patient-regarding preferences by testing the null hypothesis that -FEMALE = -MALE .…”
Section: Patient-regarding Preferencesmentioning
confidence: 64%
“… See, e.g., Hennig-Schmidt et al (2011),Godager and Wiesen (2013), Hennig-Schmidt and Wiesen (2014),Godager et al (2016),Brosig-Koch et al (2016,Wang et al (2020),Ge & Godager (2021b) andGe et al (2022) …”
mentioning
confidence: 99%
“…Other studies show how the risk attitudes (Martinsson and Persson, 2019) and altruistic tendencies of physicians (Brosig-Koch et al, 2017;Godager and Wiesen, 2013;Martinsson and Persson, 2019) might mitigate this profit-taking motive or under-provision of medical care due to a lack of monetary incentives. Our paper adds to the growing literature measuring physician altruism (Attema et al, 2023;Byambadalai et al, 2023;Ge et al, 2022;Ge and Godager, 2021;Li, 2018;Li et al, 2017) and determining whether such measures promote patient welfare at the cost of the physician's profit 1 . Previous research on hospital care have shown that prosocial doctors are less likely to be concerned with profit and more for the welfare of the patient.…”
Section: Introductionmentioning
confidence: 98%